ANALISIS PENGARUH EFEKTIVITAS DAN EFISIENSI IMPLEMENTASI TEKNOLOGI INFORMASI KOMPUTER, MEDIA INTERAKSI ONLINE, DAN KOMUNIKASI BISNIS TERHADAP PRODUKTIVITAS BISNIS PERCETAKAN DIGITAL PRINTING AND ADVERTISING Studi Kasus CV. Grafiti Stamp Advertindo - Susantie, Firna; Sitepu, Mimpin; Astuti, Nelly (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this research is to know how big an influence the Effectiveness and Efficiency of the independent variable which is Computer Information Technology, online interaction media, and business Communication influence the dependent variable which is Business Productivity. This research is run by using quantitative data analysis, statistical test analysis, multiple linear regression analysis, and coefficient of determination analysis. The data used in this study is Primary data. Statistical data processing using SPSS Version 22 The result of data processing stated that the variable of Computer Information Technology partially has a positive and significant influence to Business Productivity with count (2,315)> t-table (1,67722) and sig 0,008 <0,05, so Ho is rejected and H1 is accepted. Online Media Interaction Variables partially have a positive and significant influence on Business Productivity with t-count (2,974)> t-table (1.67722) and sig 0.006 <0.05, so Ho is clearly rejected and H1 accepted. Business Communication Variables partially have a positive and significant influence on Business Productivity with t-count (2,743)> t-table (1,67722) and sig 0,009 <0,05, so Ho is clearly rejected and H1 accepted. Simultaneously, Computer Information Technology, Online Interaction, and Business Communication variables have a positive and significant influence on Business Productivity with the value obtained Fcount (4,782)> Ftable (2.81) and Sig (0.006) <0,05, Ho is rejected and H1 accepted. For R square, the value of 0,721 or 72,1% means the independent variable can influence or explain the dependent variable together 72,1%, and the rest 27,9% can be explained by another independent variable not used in research.